Does people’s participation enhance the success of watersheds? A comprehensive assessment - CHAND, PREM; MEENA, DINESH CHAND (Journal of Soil and Water Conservation, 2024)
Watershed development is one of the best approaches to restoring degraded land, reducing poverty, providing better livelihoods, and improving the biophysical and socio-economic environment. The Government and academicians are more interested in including local and scientific knowledge through more participation of local people in watershed management activities. This paper assessed how watershed institutions evolved to ensure people’s participation to achieve greater success in watershed management, and how the focus & approach of watershed management and institutional arrangement evolved. The study further sees the role of institutional arrangement in ensuring people’s participation. Results show that integrating local knowledge through people participation is a prerequisite for watersheds’ success and sustainable management. Watersheds with high people participation delivered high ecosystem services than those with little participation. Despite revising the watershed guidelines several times to incorporate local knowledge, the desirable people’s participation level still needs to be achieved. There is a need to bring together formal scientific watershed management approaches and informal community knowledge for better planning, acceptance, and ownership by the local people. The watershed has primarily been treated as technology, but its management remains a significant bottleneck. Institutional innovations are needed to ensure people’s participation, requiring more research on watershed institutions.